Multimodal Pencitraan Anies Baswedan dalam Akun Instagram @aniesbaswedan Menjelang Pemilihan Presiden 2024 - Natalia Reviyanti (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2023)
The aim of this research is to analyze the visual depiction of Anies Baswedan on Instagram and highlight the role of social media in political campaign strategies. The method used is a qualitative approach with an interpretive paradigm, with a multimodality research method with a Systemic Functional Linguistics (SFL) research design. The results of this research are an analysis of three photos uploaded to the Instagram account @aniesbaswedan which depict Anies Baswedan's political activities and campaign as a presidential candidate. Ideation, interpersonal, and textual analyzes are used to study the use of language and images in the context of political drama via social media. In conclusion, this research provides an understanding of the content and interactions that occur in @aniesbaswedan's Instagram uploads, and these photos receive a positive response from social media users. Anies Baswedan uses Instagram as a stage to show his existence in the world of politics, and he uses these uploads to achieve the goal of being accepted by other users. The photos uploaded by Anies show characteristics that match the purpose of the scene regarding his dream of becoming president. Via Instagram, Anies Baswedan appears as a candidate who is ready to become President 2024 with a serious, warm and humanist image.